ISOLASI DAN SKRINING BAKTERI SELULOLITIK DARI BEBERAPA TANAH HUTAN DI BALI - Yusnia, Ella Dewi; Wayan Gunam, Ida Bagus; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p02, 2019)
Soil is one habitats of the cellulolytic bacteria. Soil containing manure and decayed wood is habitation for cellulolytic bacteria.  This research is aimed to isolate and screen cellulolytic bacteria from the soil in Bali that has the potentials to degrade cellulose. The soil samples ware taken from forest in Gunaksa-Klungkung, Telaga-Karangasem, Sukahat-Karangasem, Gilimanuk-Jembrana, and Mangrove forests in Suwung-Denpasar. Each single cellulolytic bacteria colonies which grown on solid media containing carboxymethyl cellulose (CMC) were isolated. Screening of cellulolytic bacteria using congo red 0,1 %, staining bacterial isolates which were created clear zones in around the colony were selected. The isolation result are 67 isolated cellulolytic bacteria covered in five soils sample. Twenty-one bacterial isolates were producing cellulase enzymes with an indication of a clear zone in around the colony. Nine superior isolates have high cellulolytic index (CI), namely: G2-8 (5.41), G1-4 (4.86), G2-10 (4.5), G2-2 (3.64), M1-5 (3.10), G2-5 (3.03), M2-12 (2.72), G1-1 (2.38), and M1-1 (2.21). The obtained highest percentage of filter paper (Whatman No.1) degradation was 8.32% and the lowest was 2.48%. Keywords : forest soil, isolation, cellulolytic bacteria, congo red